2018
DOI: 10.31093/jraba.v3i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Erp System Adoption Determinants

Abstract: Penelitian ini menguji faktor-faktor yang mempengaruhi penggunaan Enterprise Resource Planning (ERP) di PT Kereta Api Indonesia area operasi 8 Surabaya. Responden penelitian ini sebanyak 70 pengguna sistem ERP. Pengujian hipotesis dilakukan menggunakan model SEM-PLS. Hasil penelitian ini menunjukkan bahwa karakteristik individu, karakteristik organisasi, dan karakteristik teknologi memiliki pengaruh positif yang signifikan terhadap manfaat yang dirasakan dari ERP dan persepsi kemudahan penggunaan ERP. Manfaat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(47 reference statements)
2
6
1
Order By: Relevance
“…Organisations that understand which factors influence ERP users' satisfaction can influence users' extended use (ExU) of the ERP system and thus attain organisations' better results and returns (Hsieh & Wang, 2007;Hsu et al, 2015;Sternad & Bobek, 2014). This differs in different cultural environments (Annamalai & Ramayah, 2013;Hancerliogullari Koksalmis & Damar, 2019;Isnalita, 2018;Krumbholz et al, 2000;Leidner & Kayworth, 2006;Rajan & Baral, 2015;Scholtz, Mahmud & Ramayah, 2016;Stuart et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Organisations that understand which factors influence ERP users' satisfaction can influence users' extended use (ExU) of the ERP system and thus attain organisations' better results and returns (Hsieh & Wang, 2007;Hsu et al, 2015;Sternad & Bobek, 2014). This differs in different cultural environments (Annamalai & Ramayah, 2013;Hancerliogullari Koksalmis & Damar, 2019;Isnalita, 2018;Krumbholz et al, 2000;Leidner & Kayworth, 2006;Rajan & Baral, 2015;Scholtz, Mahmud & Ramayah, 2016;Stuart et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing past ERP literature studies regarding TAM, we found that different studies have researched ERP acceptance by users (Huang & Yasuda, 2016;Schlichter & Kraemmergaard, 2010). They have researched different issues of ERP use and have been focused on a small (limited) number of factors that have an influence on ERP acceptance in different phases of an ERP system life-cycle (Alhadi & Al-Shaibany, 2017;Amoako-Gyampah & Salam, 2004;Bazhair & Sandhu, 2015;Bradley & Lee, 2007;Bueno & Salmeron, 2008;Calisir et al, 2009;Hancerliogullari Koksalmis & Damar, 2019;Hsieh & Wang, 2007;Isnalita, 2018;Kwahk & Lee, 2008;Lee et al, 2010;Mayeh et al, 2016;Nah et al, 2004;Sun et al, 2009;Uzoka et al, 2008;Youngberg et al, 2009;Weli, 2019).…”
Section: Theoretical Background and Conceptual Research Modelmentioning
confidence: 99%
See 3 more Smart Citations